Batman : the complete animated series [videorecording (Blu-Ray)] - Altieri, Kevin; Timm, Bruce; Timm, Bruce; Kane, Bob (Warner Bros. Entertainment, 2018)
Batman fights evil villains and protects the people of Gotham City.